The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0004-27302008000600019
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypertension and hypokalemia as first clinical manifestations in ectopic Cushing's syndrome

Abstract: Ectopic ActH production occurs in about 10% of all cases of cushing's syndrome, and about 25% of cases of ActH-dependent cushing's syndrome. diverse tumor types are able to produce ActH ectopically, including small cell lung carcinoma. Ectopic ActH secretion by malignant neoplasm has been reported to have earlier and more aggressive metabolic effects. We report a 59-year-old male patient with severe hypertension, metabolic alkalosis and hypokalemia as the first clinical manifestations of an ActH-secreting smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Hypokalemia occurred if there was severe hypercortisolism in both CD and ectopic ACTH patients. 4,9,18,[25][26][27][28] Moreover, the UFF/UFE ratio in patients with hypokalemia was significantly higher than that in adrenal CS patients with normokalemia (P < 0.001), suggesting that 11β-HSD2 deficiency was ACTH independent. 29 Otherwise, we analyzed the incidence of hypokalemia in patients hospitalized in our department with ACTH-independent cortisol-secreting adrenal adenoma and carcinoma.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hypokalemia occurred if there was severe hypercortisolism in both CD and ectopic ACTH patients. 4,9,18,[25][26][27][28] Moreover, the UFF/UFE ratio in patients with hypokalemia was significantly higher than that in adrenal CS patients with normokalemia (P < 0.001), suggesting that 11β-HSD2 deficiency was ACTH independent. 29 Otherwise, we analyzed the incidence of hypokalemia in patients hospitalized in our department with ACTH-independent cortisol-secreting adrenal adenoma and carcinoma.…”
Section: Discussionmentioning
confidence: 91%
“…The results above indicated that ACTH was not as relevant as cortisol in contributing to hypokalemia. Hypokalemia occurred if there was severe hypercortisolism in both CD and ectopic ACTH patients . Moreover, the UFF/UFE ratio in patients with hypokalemia was significantly higher than that in adrenal CS patients with normokalemia ( P < 0.001), suggesting that 11β‐HSD2 deficiency was ACTH independent…”
Section: Discussionmentioning
confidence: 96%
“…In the majority of patients, hypokalemia is the first clinical manifestation of EAS [17,18]. In the case reported in this paper, hypokalemia and muscle weakness of the bilateral legs were clinically detected during the course of chemotherapy but not at the time of initial diagnosis.…”
Section: Discussionmentioning
confidence: 57%
“…The authors report on a case of a patient that presented with severe hyperglycemia and refractory hypokalemic metabolic alkalosis that upon investigation was compatible with CD. In the case reports that have described a similar presenting clinical picture, the underlying cause was always ectopic ACTH secretion (7)(8)(9)(10). The diagnosis of CD was unexpected; therefore, we believe that this case report is noteworthy.…”
Section: Introductionmentioning
confidence: 63%